THE SECONDARY EFL TEACHERS’ TEACHING STRATEGIES DURING COVID-19 OUTBREAK - Imansyah, Imansyah; Utama, I Made Permadi (Jurnal Penelitian Humaniora, 2023)
This research aimed at investigating the secondary EFL teachers’ teaching strategies during COVID-19 outbreak and figuring out the problems faced in implementing the teaching strategies during COVID-19. This research was designed as qualitative research. The subjects of this research were the secondary EFL teachers at SMP N 4 Kopang selected based on certain criteria. The data were collected through interview and documentation. This research used data condensation, data display, and drawing conlusion as technique of data analysis.  Based on research finding, the strategies implemented by the secondary teachers during COVID-19 were situated teaching and picture description. Those strategies were effective, easy to plan and the students enjoyed the class. Lack of  learners’ motivation, insuficient time, resources and materials were the problems faced by the teachers in teaching English. The strategies above used in general material and affected all aspects such as speaking, listening, reading, and writing. Moreover, Teachers as educators should be able to synergize a learning activity with the learning method used in every situation. It can support the students’ skill in the process oriented material that will be taught.